Незамерзшие цветы: Рассказы / Роман Валишин ; [сост. Г. В. Романова] - Валишин Роман Галяскарович (Удмуртия, 2004)
Экземпляры: с/ф № 1 () / Инвентарный номер: 33140 / Цена: / Сис.шифр: 84Удм / Авт.знак: В 15 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Удм)6